2015
DOI: 10.1039/c5nr02696b
|View full text |Cite
|
Sign up to set email alerts
|

Stable and efficient colour enrichment powders of nonpolar nanocrystals in LiCl

Abstract: In this work, we propose and develop the inorganic salt encapsulation of semiconductor nanocrystal (NC) dispersion in a nonpolar phase to make a highly stable and highly efficient colour converting powder for colour enrichment in light-emitting diode backlighting. Here the wrapping of the as-synthesized green-emitting CdSe/CdZnSeS/ZnS nanocrystals into a salt matrix without ligand exchange is uniquely enabled by using a LiCl ionic host dissolved in tetrahydrofuran (THF), which simultaneously disperses these no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…On the other hand, 2ML CdSe NPLs synthesized using excess amount of Se exhibit almost purely broadband PL emission centered at ≈535 nm with a FWHM of ≈150 nm as shown in Figure a and a QY of 90% in solution. QY measurements were executed by following the procedure developed by De Mello et al at an excitation wavelength of 380 nm . We performed PL excitation (PLE) spectroscopy to probe the origin of the broadband emission.…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, 2ML CdSe NPLs synthesized using excess amount of Se exhibit almost purely broadband PL emission centered at ≈535 nm with a FWHM of ≈150 nm as shown in Figure a and a QY of 90% in solution. QY measurements were executed by following the procedure developed by De Mello et al at an excitation wavelength of 380 nm . We performed PL excitation (PLE) spectroscopy to probe the origin of the broadband emission.…”
Section: Resultsmentioning
confidence: 98%
“…[40] We measured the fluorescence quantum yield of the polymer and polyrotaxane solutions in water using the method described in refs. [30] and [41].…”
Section: Optical Characterizationsmentioning
confidence: 99%
“…Otto et al showed that the quantum dots in water can be successfully incorporated into crystalline salt matrices. Later, this approach was shown to improve the fluorescence QY, and emission stability . Moreover, this method was also extended to nonionic crystals including sucrose and anthracene and to quantum dots in nonpolar solvents and applied in light‐emitting diodes (LEDs) and sensors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it is well known that such a ligand exchange procedure can significantly decrease the efficiency of the QDs. Our group addressed this issue by specifically employing LiCl as the host matrix [35], which can be dissolved in tetrahydrofuran. Since the nonpolar QDs can also be dispersed in tetrahydrofuran, incorporation of the nonpolar QDs into LiCl has been possible without ligand exchange.…”
Section: Color-converting Colloidal Materials For Lightingmentioning
confidence: 99%